Cardiac structural and functional remodeling in the fetuses associated with maternal hypothyroidism during pregnancy. (31st December 2023) - Zhang, Yanhong; Zhang, Lisi; Zhao, Wei; Li, Na; Chen, Guihong; Ge, Jun; Su, Xingna; Ge, Shuping; Sun, Congxin
Abstract: Objectives: We sought to investigate the effect of maternal hypothyroidism during pregnancy on fetal cardiac structural and functional remodeling using fetal echocardiography. Methods: A total of 59 pregnant women with history of hypothyroidism were prospectively enrolled as the study group, and 74 normal fetuses as the control group. Fetal echocardiography was performed on each subject. Demographic, clinical, and fetal echocardiographic variables were measured, including left ventricular (LV) and right ventricular (RV) free wall and ventricular septal thickness, fractional shortening (FS), stroke volume (SV), cardiac output (CO), combined cardiac output (CCO), cardiac index (CI), combined cardiac index (CCI), aortic and pulmonary artery velocity, ductus venosus (DV) and pulmonary vein (PV) spectral Doppler, and Tei index. Results: The incidence of echogenic intracardiac foci (EIF) was higher in the study group than that in the control group (18.6% vs. 6.8%, p  = .036). The thickness of LV free wall and interventricular septum was reduced, the pulmonary velocities and CCI, RV FS, CO, and CI were lower, the S, D, S/A, and pulsatility index (PI) of DV were higher, and LV Tei index was higher in the study group compared with the control group. There was no significant difference in other variables between the two groups. Conclusions: There is cardiac remodeling, and systolic, diastolic functional alterations in fetuses with maternal hypothyroidism. Further investigation is warranted to develop strategies to optimize the outcome of these fetuses.